1967
DOI: 10.1677/joe.0.0390115
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Blockade of the Initiation but Not of the Maintenance of Sexual Receptivity of the Ewe

Abstract: 1965) have shown that chlorpromazine effectively blocks ovulation in the ewe when administered immediately after the animals had become sexually receptive. From the results of Robertson & Rakha (1966) it appears that the suppressive action of chlorpromazine was very likely related to the blockade of the ovulatory release of luteinizing hormone (LH) that occurs at this time. Their results indicate also that there is a discharge of follicle-stimulating hormone (FSH) from the pituitary prior to oestrus, and it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…All four groups had an average of (Smeaton & Robertson, 1971), but also the number of follicles which mature is unaffected by a 50",, reduction in the number available 3 days before the onset of oestrus. The shortterm nature of ovarian compensation in the sheep is apparently similar to that observed for the hamster (Greenwald, 1962) Buttle & Robertson (1967) found that the onset of oestrus in Cheviot ewes was blocked by 12 mg chlorpromazine/kg followed by 4 mg/kg every 6 hr, whereas the display of oestrus and the duration of the cycle were unaffected in the present experiment. The absence of an effect of chlorpromazine on the secretion of progesterone by the CL of hysterectomized ewes was taken to indicate that prolactin rather than LH is luteotrophic in the sheep (Coudert & Short, 1968) Land, 1971), arising from a reduced sensitivity to inhibitory mechanisms.…”
Section: Chlorpromazinesupporting
confidence: 86%
“…All four groups had an average of (Smeaton & Robertson, 1971), but also the number of follicles which mature is unaffected by a 50",, reduction in the number available 3 days before the onset of oestrus. The shortterm nature of ovarian compensation in the sheep is apparently similar to that observed for the hamster (Greenwald, 1962) Buttle & Robertson (1967) found that the onset of oestrus in Cheviot ewes was blocked by 12 mg chlorpromazine/kg followed by 4 mg/kg every 6 hr, whereas the display of oestrus and the duration of the cycle were unaffected in the present experiment. The absence of an effect of chlorpromazine on the secretion of progesterone by the CL of hysterectomized ewes was taken to indicate that prolactin rather than LH is luteotrophic in the sheep (Coudert & Short, 1968) Land, 1971), arising from a reduced sensitivity to inhibitory mechanisms.…”
Section: Chlorpromazinesupporting
confidence: 86%
“…The time difference can be explained partially by the mean delay of approximately 14 h in the time of onset of oestrus, caused by laparotomy. There are three possible explanations : (a) an interruption of the supply of oestrogen to the hypothalamus due to the cannulation procedure and resultant damage to the ovarian vein; (b) a block in the mechanism of follicle-stimulating hormone (FSH) release; or (c) a residual effect of the anaesthetic on the oestrogen-sensitive behaviour centre (Buttle & Robertson, 1967). The data of Moore et al (1969) are based on the observed time of onset of oestrus while those reported here are based on the anticipated time, making allowance for the delay in oestrus after laparotomy, a phenomenon since confirmed in this laboratory (C. Jaume, personal communication).…”
Section: Chemical Analysismentioning
confidence: 99%